Determinant of Islamic Pension Fund In Indonesia - Aziz, Roikhan Mochamad; Jayaprawira, Acep R.; Sulistyowati, Sulistyowati (Faculty of Islamic Economics and Business of Institut Agama Islam Negeri (IAIN) Pekalongan, 2019)
The research aims to know the variables that affect the assets of Pension Funds by Financial Institutions (DPLK, Pension funds by financial institution) Muamalat, which is the performance of Bank Muamalat as internal factors that described in the variable Profit of Bank Muamalat and third-party funds. The external factors are Bank Indonesia Sharia Certificates (SBIS, Sertifikat Bank Indonesia Syariah) as an indicator of the placement of Islamic funds, and profit of DPLK Muamalat as a religious factor.The method used in this research is done by Multiple Correlation Regression Analysis with monthly data starting from April 2008 (since the existence of SBIS) until October 2017. Moreover, Analysis Method of HahSlm Theory is added which is an analysis that approached according to Islamic thinking model to provide a benchmark that corresponds to the religious value.The final result of this study emphasizes that all factors, which consist of the internal factors, external factors and religious factors, affect the assets of DPLK Muamalat. It is interesting to know that the profit of Bank Muamalat has a negative correlation. That is certainly not in accordance with the existing theory that performance or credibility of the main business (Bank Muamalat) has a big influence on the performance of DPLK Muamalat. It is expected that the results of the research is useful for every party, from the regulator party like the Financial Services Authority (OJK, Otoritas Jasa Keuangan), the industrial parties (the other DPLK), the company, and the participants of the Pension Funds by Financial Institutions.